Evidence of the mid-latitude impact of Antarctic ozone depletion - Atkinson, Roger J.; Matthews, W. Andrew; Newman, Paul A.; Plumb, R. Alan (1989)
Record low ozone values found over Australia and New Zealand during December 1987 following the record low Antarctic values of October 1987 are analyzed. The sudden decline of ozone amounts in midmonth rule out photochemical effects as a cause and permit the underlying processes to be investigated on a case study basis. Using data from ozone sondes, radiosondes, the Nimbus-7 total ozone mapping spectrometer, and meteorological analyses from the National Meteorological Center, it is argued that these low values resulted from transport of ozone-poor air from higher latitudes. Thus, it seems that the chemical destruction of ozone over Antarctica in early spring is having an impact on lower latitudes.